Colégio Estadual Barão do Rio Branco de Foz do Iguaçu: a resistência contra o fechamento do curso de magistério (1997-2004) - Nascimento, Maura Sandra da Silva do (2022)
The High School Expansion Program in Paraná (PROEM), the result of an agreement between the State government and the Inter-American Development Bank (IDB), provided for the reformulation of High School through the closing of all technical courses, resulting in the proposal to close of the Teaching Course of the State College Barão do Rio Branco. This work rescues the history of the resistance movement to the closing of the course, which began among education workers and the school community. Given the success of the resistance movement, Colégio Estadual Barão do Rio Branco did not fail to contribute to the training of part of the population of the city of Foz do Iguaçu, becoming the only school of basic education in the city to offer the Training Course of Teachers. The research investigates how the process of resistance to the closing of the teaching staff of Colégio Estadual Barão do Rio Branco took place between 1997 and 2004. For this, it discusses educational policies and presents interviews with teachers who were part of the resistance movement. The theoretical and methodological conception adopted is dialectical materialism, based on the following categories: historicity, democratic management and resistance action. It is concluded that the fundamental factors for the movement of resistance to the closing of the course to be successful were: the relationship between the school and the university and union, critical training, knowledge about legislation, the participation of the school community and democratic management.